Complications of the recovery period after arthroscopic reconstruction of the anterior cruciate ligament - A. O. Pavlov; A. D. Strelcov; S. V. Prokopenko; E. V. Portnyagin; E. Yu. Mozheyko; N. K. Komarova; A. N. Narkevich (Спортивная медицина: наука и практика, 2021)
A review of the literature is devoted to the problem of complications after arthroscopic reconstruction of the anterior cruciate ligament. The authors covered questions of epidemiology and surgical technique, touched on important aspects of the main complications, such as graft damage, arthrofibrosis and impingement syndrome, the formation of synovial cysts, infections, the development of osteoarthritis and cartilage degeneration. Despite the prevalence of pathology, a huge number of publications and the development of arthroscopic surgery, there are many theoretical and technical problems, that have not yet found a satisfactory solution and require further development. A relevant question for the doctor is the problem of correctly choosing the method or combination methods for anterior cruciate ligament reconstruction in relation for each patient, considering the individual characteristics and possible risks of developing different complications in patient.